Given:
The quadratic equation is
![0=-3x^2-4x+5](https://img.qammunity.org/2021/formulas/mathematics/college/xkcdklfbd2sgyt79rceqm0z8lht93jtxz2.png)
To find:
The simplest radical form of the solution.
Solution:
Quadratic formula:
If a quadratic equation is
, then
![x=(-b\pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j7q8ukifcxvxh2kygesnwxbt4ycpyqzef0.png)
We have,
![0=-3x^2-4x+5](https://img.qammunity.org/2021/formulas/mathematics/college/xkcdklfbd2sgyt79rceqm0z8lht93jtxz2.png)
Here, a=-3, b=-4 and c=5. Putting these values in the quadratic formula, we get
![x=(-(-4)\pm √((-4)^2-4(-3)(5)))/(2(-3))](https://img.qammunity.org/2021/formulas/mathematics/college/m9xksjyg2dl23ppig0p7moo60faoasr9cg.png)
![x=(4\pm √(16+60))/(-6)](https://img.qammunity.org/2021/formulas/mathematics/college/v0ygveeg0ctvpws0qlqq67sfx1sj2ev5ba.png)
![x=(4\pm √(76))/(-6)](https://img.qammunity.org/2021/formulas/mathematics/college/mxrjto7i3o5o863zuozosh1s5cg1wr63bg.png)
![x=(4\pm 2√(19))/(-6)](https://img.qammunity.org/2021/formulas/mathematics/college/j82vw8w8e6gguscf6ar95hxebhpg6itvru.png)
Taking 2 common, we get
![x=(2(2\pm √(19)))/(-6)](https://img.qammunity.org/2021/formulas/mathematics/college/xzd64970sc2vw88sbc4hnr1u3u2y7ci6ay.png)
![x=((2\pm √(19)))/(-3)](https://img.qammunity.org/2021/formulas/mathematics/college/xy7h8pzhkigmeazm07h86v88e6rbn2zxe9.png)
![x=-((2\pm √(19)))/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/igevb66i9jmzeyavdff3yboe5nmktztj7h.png)
Therefore, the correct option is A.